Twice bitten - Sands, Lynsay (Sands, Lynsay. Argeneau series., 2018)
"For someone whos been around for over a hundred and forty years, immortal Elspeth Argeneau hasn't done a whole lot of living. Now that shes moved away from her controlling mother, shes tracking down rogue vampires and enjoying some overdue freedom. A fling would be fun. A life mate can wait. Yet to Elspeths surprise, her landlady's hot grandson checks both boxes." -- goodreads.com